Pleural tuberculosis: A concise clinical review - Shaw, Jane A.; Irusen, Elvis M.; Diacon, Andreas H.; Koegelenberg, Coenraad F. (The clinical respiratory journal, 2018)
Tuberculosis (TB) is the leading infectious cause of death worldwide, and the commonest cause of death in people living with HIV. Globally, pleural TB remains one of the most frequent causes of pleural exudates, particularly in TB‐endemic areas and in the HIV positive population. Most TB pleural effusions are exudates with high adenosine deaminase (ADA), lymphocyte‐rich, straw‐coloured and free flowing, with a low yield on mycobacterial culture. TB pleurisy can also present as loculated neutrophil‐predominant effusions which mimic parapneumonic effusions. Rarely, they can present as frank TB empyema, containing an abundance of mycobacteria. Up to 80% of patients have parenchymal involvement on chest imaging. The diagnosis is simple if M. tuberculosis is detected in sputum, pleural fluid or biopsy specimens, and the recent advent of liquid medium culture techniques has increased the microbiological yield dramatically. Where the prevalence of TB is high the presence of a lymphocyte‐predominant exudate with a high ADA has a positive predictive value of 98%. In low prevalence areas, the absence of an elevated ADA and lymphocyte predominance makes TB very unlikely, and pleural biopsy should be performed to confirm the diagnosis. Pleural biopsy for liquid culture and susceptibility testing must also be considered where the prevalence of drug resistant TB is high. Treatment regimens are identical to those administered for pulmonary TB. Initial pleural drainage may have a role in symptom relief and in hastening the resolution of the effusion. Surgical intervention may be required in loculated effusions and empyemas.